HYDROGELS THE THREE DIMENSIONAL NETWORKS: A REVIEW - M., TRINADHA RAO; CHVS, PHANINDRA; M., YAMINI; C. H., PRASAD (International Journal of Current Pharmaceutical Research, 2021)
Hydrogel products constitute polymeric materials as a group, the hydrophilic structure which renders them the capability of holding large amounts of water in their 3-dimensional networks. Extensive employment of those products during a number of commercial and environmental areas of application is taken into account to be of prime importance. Needless to say, natural hydrogels were gradually replaced by synthetic types thanks to their higher water absorption capacity, long service life, and wide sorts of raw chemical resources. Literature on this subject was found to be expanding, especially within the scientific areas of research. However, variety of technical reports publications and handling hydrogel products from the points of view of engineering were examined to overview technological aspects covering this growing the field of research. the first objective of this text is to review the literature concerning classification of hydrogels on different bases, chemical characteristics and physical characteristics of those products, and technical feasibility of their best utilization. It also involved the technologies adopted for hydrogel production along-side process and design implications, optimized conditions, and the block diagrams of the preparation process. Recent forms of hydrogel material generations are also presented in some details that are innovative in nature.